FOOD AND NUTRITION MISINFORMATION IN INTERNET: A CASE OF SAFETY OF ASPARTAME INTAKE - Afriansyah, Nurfi (GIZI INDONESIA, 2007)
Food and nutrition (FN) misinformation is the incomplete, incorrect, or misleading informationabout FN science, without any scientific evidence. Misinformation can easily be taken frominternet, and can come from food industries, friends, families, and influenced by its culture.Information on negative aspect of aspartame consumption is a case of food and nutritionmisinformation taken from internet. Searching information through websites on the topic ofaspartame will be easily found but most of the information claimed that using aspartamesweeteners is a frightening personal account attributing multiple health disasters, even theevidence has not been established yet. The aim of this article is to review food and nutritionmisinformation, with the emphasis on the association between aspartame intake and its effect onhealth.Key words: food and nutrition misinformation; aspartame intake